Coverage of a Crisis: The Effects of International News Portrayals of Refugees and Misuse of the Term "Immigrant". (April 2018) - Hoewe, Jennifer
Given the intense debate surrounding the United States' policies regarding admission of refugees and immigrants into the country, this study set out to determine how the news media cover refugees and how that coverage influences news consumers. This research examines how news stories informed the public about the individuals affected by the wars in Syria, Afghanistan, and Iraq. In particular, it explores usage of the word "refugee" as opposed to "immigrant" to determine how individuals fleeing their home countries were described by the press. A content analysis revealed that U.S. newspapers were more likely than international newspapers to conflate the term "immigrant" with "refugee." Also, when refugees were incorrectly described as "immigrants, " references to terrorism were more likely. The experimental portion of this research tested how news consumers respond to this framing of "refugee" versus "immigrant" in the same war-torn situation. Democrats, Independents, and Republicans who read about individuals labeled as "refugees" did not distinguish them from "immigrants" in the same situation, indicating they may have adopted the U.S. news media's conflation of these terms. Republicans, however, had more negative perceptions of both refugees and immigrants than did Democrats or Independents, reporting greater perceptions of threat and favoring more stringent policy. These results suggest that American news consumers do not distinguish between refugees and immigrants in terms of policy, which at least partially implicates U.S. news media for not providing a solid benchmark for understanding these groups of people.